2019
DOI: 10.4253/wjge.v11.i7.427
|View full text |Cite
|
Sign up to set email alerts
|

Should a colonoscopy be offered routinely to patients with CT proven acute diverticulitis? A retrospective cohort study and meta-analysis of best available evidence

Abstract: BACKGROUND The current guidelines suggest that patients should undergo endoscopic evaluation of the colonic lumen after an episode of computed tomography (CT) proven acute diverticulitis to rule out malignancy. The usefulness of routine endoscopic evaluation of CT proven diverticulitis remains unknown. AIM To establish whether routine colonoscopy should be offered to patients after an episode of diverticulitis. METHODS We performed a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…Further, we reported the following prevalences for polyps: Polyp 22.7% (21 studies, 95%CI: 19.6%-16.0%), hyperplastic polyp 9.2% (13 studies, 95%CI: 7.6%-11.2%), adenoma 14.2% (15 studies, 95%CI: 11.8%-17.1%) and advanced adenoma 4.4% (8 studies, 95%CI: 3.4%-5.8%)[ 2 , 3 ]. We note that these prevalences are higher than the prevalence reported by Asaad et al[ 1 ] in patients suffering from diverticulitis.…”
Section: To the Editorcontrasting
confidence: 74%
See 3 more Smart Citations
“…Further, we reported the following prevalences for polyps: Polyp 22.7% (21 studies, 95%CI: 19.6%-16.0%), hyperplastic polyp 9.2% (13 studies, 95%CI: 7.6%-11.2%), adenoma 14.2% (15 studies, 95%CI: 11.8%-17.1%) and advanced adenoma 4.4% (8 studies, 95%CI: 3.4%-5.8%)[ 2 , 3 ]. We note that these prevalences are higher than the prevalence reported by Asaad et al[ 1 ] in patients suffering from diverticulitis.…”
Section: To the Editorcontrasting
confidence: 74%
“…We think that the opposing conclusions reached by Asaad et al[ 1 ] might be explained by limitations in their study design, as they have reported in their publication. First, we believe that the number of patients suffering from diverticulitis included by the authors over a three-year period in three centers is too small and that their study is insufficiently powered to show any difference with reference patients.…”
Section: To the Editormentioning
confidence: 70%
See 2 more Smart Citations
“…These findings are in line with the recommendations from the World Society of Emergency Surgery [2]. Currently, multidetector CT is widely used for the diagnosis of diverticulitis and its complications, with high sensitivity and specificity, leading to a better evaluation of the affected colonic segment and a selective approach to colonoscopy [3,4].…”
supporting
confidence: 81%